Family reintegration of adolescents: unsuccessful processes - Siqueira, Aline Cardoso; Massignan, Lucianna Tortorelli; Dell'Aglio, Débora Dalbosco (Paidéia (Ribeirão Preto), 2011)
This study investigates the process concerning the unsucessful family reintegration and subsequent re-institutionalization of two adolescents. Case studies were carried out based on interviews with the adolescents and informal interviews with the shelters technicians and supervisors. The results indicate similarities in the reintegration processes, such as a lack of previous evaluation of the situation, taking into account the familys and the adolescents motivations concerning the process, as well as a lack of systematic follow-up during the reintegration period. Public policies toward this process are suggested in order to avoid new ruptures of bonds and to ensure the right of institutionalized young individuals to a family life.